2020
DOI: 10.3390/app10072383
|View full text |Cite
|
Sign up to set email alerts
|

Distributed Passive Actuation Schemes for Seismic Protection of Multibuilding Systems

Abstract: In this paper, we investigate the design of distributed damping systems (DDSs) for the overall seismic protection of multiple adjacent buildings. The considered DDSs contain interstory dampers implemented inside the buildings and also interbuilding damping links. The design objectives include mitigating the buildings seismic response by reducing the interstory-drift and story-acceleration peak-values and producing small interbuilding approachings to decrease the risk of interbuilding collisions. Designing high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Sanghai & Pawade (2021) and Miguel & Pérez (2017(, approved that the displacement reductions are about 80% for 4, 9, and 10 stories scenarios. Palacios et al (2020) reported about 50% and 40% reductions in the overall inter story-drift and acceleration peak-value, respectively. Kim & An (2016) concluded that maximum roof displacement and the inter-story drift ratio were reduced by 30% and 40%, respectively.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Sanghai & Pawade (2021) and Miguel & Pérez (2017(, approved that the displacement reductions are about 80% for 4, 9, and 10 stories scenarios. Palacios et al (2020) reported about 50% and 40% reductions in the overall inter story-drift and acceleration peak-value, respectively. Kim & An (2016) concluded that maximum roof displacement and the inter-story drift ratio were reduced by 30% and 40%, respectively.…”
Section: Resultsmentioning
confidence: 96%
“…However, the results showed that the average displacement decreased by approximately 82%. Palacios et al (2020) worked on protecting multiple adjacent buildings by using distributed damping systems. They reported about 50% in the overall inter story-drift of 40% in the overall acceleration peak-value.…”
Section: Introductionmentioning
confidence: 99%
“…The inerter modifies the inertial properties of the structures while adding negligible physical mass, and it may be a cost-effective solution for both seismic [2,4] and wind [1,3] vibration control. Some other papers concern the development of efficient design methods that exploit state-of-the-art algorithms and solvers for the optimization of the devices [11,13]. One paper concerns the challenging task of designing lead rubber bearings considering different performance requirements [10].…”
Section: Editorialmentioning
confidence: 99%
“…In paper [13], Palacios-Quiñonero et al develop an optimal passive actuation scheme of multibuilding systems composed of both interstory and interbuilding linear viscous dampers. Unlike other literature studies that are limited to one or at the most two adjacent buildings, the paper addresses a set of five identical planar frames.…”
Section: Editorialmentioning
confidence: 99%
“…Recent works in that line include ISSD designs based on a wide variety of optimization objectives, such as structural performance [21], energy dissipation [22], total-building performance [23], retrofitting cost [24] and structural reliability [25]. Advanced ISSD designs consider soil-structure interactions [26], irregular 3D structures [21] and multi-building problems [27,28]. Enhanced design strategies include simplifying procedures to deal with the high computational cost in nonlinear studies [29], design methodologies based on active control approaches [30,31] and special seismic excitation schemes [32].…”
Section: Introductionmentioning
confidence: 99%